'A synergy model of health': an integration of salutogenesis and the health assets model. (24th September 2020) - Pérez-Wilson, Patricia; Marcos-Marcos, Jorge; Morgan, Antony; Eriksson, Monica; Lindström, Bengt; Álvarez-Dardet, Carlos
Summary: This article proposes to advance the connections between salutogenic theory and assets models for health improvement. There is a need to integrate their use in public health and health promotion so that their respective potentials can be fully developed. This requires their synergies to be made more explicit so that a more coherent approach can be taken to their utilization. A mechanism is therefore needed that helps to raise awareness of them and their value as a resource together. Bronfenbrenner's bioecological theory provides one framework that can support better integration of salutogenesis with the applied nature of assets-based models. This paper proposes a new 'synergy model for health' that integrates key concepts associated with salutogenic theory—generalized and specific resistance resources (GRRs/SRRs) and generalized and specific resistance deficits and the sense of coherence (SOC). In doing so, it highlights those GRRs and SRRs which are assets that, either individually or collectively, help to develop a stronger SOC. Higher levels of SOC can then support the transformations of potential resources into available assets (that people can understand, manage and make sense of), capable of producing positive health development. The proposed 'Synergy model of health' aims to contribute to a deeper theoretical understanding of health and development through the integration of the key elements of both salutogenesis and assets models. This can facilitate a better contextualization of the ideas into public health policy and practice by making the salutogenic theory more action-oriented and the assets model more theoretical.